2010
DOI: 10.1074/jbc.m109.032771
|View full text |Cite
|
Sign up to set email alerts
|

Human Biliverdin Reductase Suppresses Goodpasture Antigen-binding Protein (GPBP) Kinase Activity

Abstract: The Ser/Thr/Tyr kinase activity of human biliverdin reductase (hBVR) and the expression of Goodpasture antigenbinding protein (GPBP), a nonconventional Ser/Thr kinase for the type IV collagen of basement membrane, are regulated by tumor necrosis factor (TNF-␣). The pro-inflammatory cytokine stimulates kinase activity of hBVR and activates NF-B, a transcriptional regulator of GPBP mRNA. Increased GPBP activity is associated with several autoimmune conditions, including Goodpasture syndrome. Here we show that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This finding suggests that hBVR itself mediates the activation of NF‐κB in the pathway. We also obtained 12 clones in this screen for the Goodpasture antigen binding protein, and we have confirmed that interaction by several independent criteria (61).…”
Section: Resultssupporting
confidence: 56%
“…This finding suggests that hBVR itself mediates the activation of NF‐κB in the pathway. We also obtained 12 clones in this screen for the Goodpasture antigen binding protein, and we have confirmed that interaction by several independent criteria (61).…”
Section: Resultssupporting
confidence: 56%
“…1e. Moreover, based on our previous study with another hBVRinteractive kinase, Goodpasture antigen-binding protein, an atypical protein kinase (57,58), it is plausible that the C-terminal segment of hBVR is involved in interaction with the Zn The Ser/Thr residues in RXX(S/T) and its related motif RXRXX(S/T) are phosphorylation targets of PKC␦, as well as CaMK2 and PKB/Akt (34,36,37). The identified substrate peptide, GLKRNRYLSFHFK, presents a new type of substrate for the PKC, and it shares with the previously identified substrates, FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…The products were separated by gel electrophoresis and detected by autoradiography. The loading for each sample was estimated by probing the blot with anti-BVR antibody, after first allowing radioactivity to decay (7,58).…”
Section: Characterization Of An Hbvr-based Peptide As a Pkc␦mentioning
confidence: 99%
“…There is also some evidence for BVR playing an indirect role in he development of autoimmunity. A yeast two-hybrid assay using BVR as the bait revealed that the Goodpasture antigen-binding protein (GPBP) was a high affinity binding partner ( Miralem et al, 2010 ). Goodpasture syndrome is one of several autoimmune diseases in which GPBP activity is increased, and is characterized by autoimmune recognition of the C-terminal non-collagenous-1 domain of the α3 chain of type IV collagen (Goodpasture antigen) in epithelial basement membranes.…”
Section: Bvr and The Immune Systemmentioning
confidence: 99%